"It's like a counselling session … but you don't need to say anything:" Exercise program outcomes for youth within a drug and alcohol treatment service. (November 2018) - More, Alissa; Jackson, Ben; Dimmock, James A.; Thornton, Ashleigh L.; Colthart, Allan; Furzer, Bonnie J.
Abstract: Objectives: Evidence for exercise as an adjunct therapy in youth substance use disorder (SUD) treatment is scarce, despite support for its efficacy among adult populations. In this study, youth undergoing residential treatment for SUDs were provided with twice-weekly exercise sessions, with the aim of examining their perceptions about the outcomes associated with regular exercise participation during their recovery. Design: Qualitative – interpretivist approach. Method: Qualitative (i.e., focus group) methods were employed to capture the experiences of 27 youth and 10 staff members employed in the facility, and content analytic procedures were employed to understand the outcomes (i.e., exercise perceptions, recovery-specific outcomes, and other health outcomes) associated with exercise participation during recovery. Results: Within three broad themes (i.e., exercise perceptions, recovery-specific outcomes, other health outcomes), youth and staff reported that, among other things, regular exercise contributed to the establishment of a healthy routine, more positive perceptions about one's appearance, improved sleep and interpersonal relationships, cathartic effects, and a sense of accomplishment. Conclusions: Based on the 'lived experiences' of youth and staff, the results of this study indicated that participation in regular, structured, and personalized exercise may be an important part of successful SUD treatment. The benefits of exercise align with a range of important outcomes including exercise perceptions (i.e., barriers to exercise participation, exercise motivation), recovery factors (e.g., cravings and withdrawals, routine), and health outcomes (e.g., self-esteem and mental health, physical health) among youth undergoing SUD treatment. Highlights: Youth enjoyed exercising and fostered the motivation to be independently active. Exercise participation was responsible for mental and physical health benefits. Youth and staff reported specific substance-related benefits of exercise. Exercise may be an important element for successful youth addiction treatment.